Development of comprehensive disease assessment in systemic vasculitis. Issue 989 (27th March 2008) - Flossmann, O; Bacon, P; de Groot, K; Jayne, D; Rasmussen, N; Seo, P; Westman, K; Luqmani, R
Abstract : The systemic vasculitides are multisystem disorders with considerable mortality and morbidity and frequent relapses. In the absence of reliable serological markers, accurate clinical tools are required to assess disease activity and damage for treatment decisions, and for the performance of clinical trials. This article reviews and summarises the development and use of disease assessment tools for determining activity and damage in systemic vasculitis and reports ongoing initiatives for further development of disease assessment tools. A literature search was conducted using PubMed and reference lists for vasculitis, assessment, clinical trials, outcome and prognosis. The findings indicate that comprehensive disease assessment in vasculitis requires documentation of disease activity, chronic irreversible damage and impairment of function.